The importance of buffer zones in woody vegetation conservation in areas that combine mega-fauna and anthropogenic disturbance: The case of Save Valley landscape, south-eastern Zimbabwe - Clayton Mashapa; Patience Mhuriro-Mashapa; Edson Gandiwa; Never Muboko; Tendai Chinho (Global Ecology and Conservation, 2021)
This study evaluated the influence of human and elephant (Loxodonta africana) utilization of woody vegetation across three land use categories; a protected conservation area (Save Valley Conservancy, SVC), a buffer zone and the adjacent communal lands of Mutema-Musikavanhu communities in the Save Valley landscape, south-eastern Zimbabwe. A total of 45 plots were assessed with 15 plots randomly placed in each of the three treatments. The following attributes were compared: tree, shrub and sapling density, tree and shrub species diversity, tree height, tree canopy cover and basal area, elephant dung density, and lastly, elephant, fire and human impacts (e.g., stump and coppicing density) on woody vegetation. Although there were no significant treatment effects (P > 0.05) on fire damage levels, number of stems per tree, alien woody plant density and coppiced woody plant density, human activities and elephant herbivory affected the rest of the measured attributes. Human and elephant herbivory disturbances were intermediate in intensity within the buffer zone where the maximum woody species diversity and the largest basal area were recorded. Elephant impact was high in the SVC and human harvesting high in the communal areas with variable negative consequences for woody vegetation (e.g., increased shrubbiness in SVC and lower tree densities in communal areas). It is likely that with an increasing population of elephants in the SVC and human population increases in Mutema-Musikavanhu communal area, severe disturbance of woodlands is likely to escalate in the Save Valley landscape. At present, the buffer zone serves as a refuge to woodlands, however there is need for continuous monitoring of woodlands across varying land use categories to inform future conservation strategies.